Reliability of the 5-min speech sample for assessing expressed emotion in Japanese patients - Uehara, Toru; Yokoyama, Tomoyuki; Goto, Masahiro; Nakano, Yasuko; Kawashima, Yoshiaki; Someya, Toshiyuki (Psychiatry and clinical neurosciences, 1999)
Expressed emotion (EE) has been shown in various countries to be a good predictor of the clinical course of a patient’s mental illness. Because the traditional EE interview requires considerable time and effort, this study examined the reliability of a method called the five‐minute speech sample (FMSS) for assessing EE. The samples of 65 subjects were rated by the FMSS–EE coding system, and the interrater reliability among four authorized raters was investigated. Of these 65 samples, 10 (15%) were rated as high‐EE (high critical, 6%; high emotional over‐involvement (EOI), 9%), and 19 (29%) were rated as borderline (b‐)‐high‐EE (b‐critical, 15%; b‐EOI, 14%). The intraclass correlation coefficient (ICC) was 0.91 for the overall category, 0.74 for criticism, 0.85 for EOI, 0.63 for b‐critical and 0.54 for b‐EOI. The FMSS was shown to be reliable for the assessment of EE, even outside of Western countries. However, the lower agreement in the subcategories of EOI and b‐critical has to be considered as a limitation of this brief method.